Annotations to Article 50 Letter (I) Law Number 5 of 1999 on The Prohibition of Monopolistic Practices and Unfair Business Competition - Nadya Rizki Emeralda; Sukarmi Sukarmi; Reka Dewantara (Jurnal Dinamika Hukum, 2020)
The discourse regarding the exception of cooperatives as an institution that is not an object in Article 50 letter i in Law Number 5 of 1999 on the prohibition of monopolistic practices and unfair business competition has been going on for a long time. The annotation of this article is seen from the incompleteness of the explanatory norm in article 50 letter i, as well as the facts on the KPPU's decisions rejecting cases that use this article as a shield. This research used normative research methods to analyze the existence and usefulness of article 50 letter i of Law No. 5 of 1999. The results of this research were in the form of juridical incompleteness and the irrelevance of this article with the sociological conditions existing in society today. Based on the economic analysis of the law, this article did not fulfill the element of effectiveness because it would only increase the submitted cases. The recommendation of this study is that there are no more exceptions to cooperatives because they are no longer in accordance with the exception reasons by the legislators at that timeKeywords: Cooperative, Unfair Business Competition, KPPU Verdict